A COLLABORATIVE CAR ON FACEBOOK GROUP: A BORDERLESS MEDIUM TO IMPROVE STUDENTS’ PRESENTATION SKILLS - Iswan Djati Kusuma; Trianda Fitria; Asri Diah Kumalawati; Dyah Retno Dwi Astuti (Politeknik Negeri Sriwijaya, 2019)
ABSTRACT: Having the ability to present well is what the employees of Frisian Flag Indonesia (FFI) are seeking from LB LIA Palembang. An outside class of 14 busy employees focuses on giving presentation successfully. Presentation skillsneed to be mastered by the participants in two weeks to present their products. Facebook group was chosen as a medium to practice the participants’presentations. After explaining the basic skills of presentation in class, all participantspresented, recorded then uploaded their presentations to Facebook group, and they were asked to watch their friends’ videos and wrote a feedback based on the designated checklist. The teacher also added the necessary comment. Theparticipants would revise and upload their presentation again based on the comments given. This research was aimed at finding out whether Facebook group is an effective borderless medium to improve students’ presentation skill for busy participants. The research was conducted in 4 cycles including uploading the first video(pretest), 2nd video, 3rd video and final presentation (post test). The result was analyzed by comparing the first presentation and the final presentation based on the designated band descriptor. The result showed that all participants improved their presentation skills by practicing and learning from each other’s pluses and minuses. Based on the questionnaire all of them like using Facebook group to practice their presentation skills because it is accessible from the comfort of their own busy schedules. Hopefully,it will inspire other teachers to embrace technology for teaching.